ISLAMIC LAW IN MALAYSIA Issues, Developments and Challenges - Mohamed Azam Mohamed Adil; Mohammad Hashim Kamali (The Malaysian Current Law Journal Sdn. Bhd., 2018)
This book described about Islamic law and practices be concern by Muslims and non- Muslims alike within multi-religious setting of Malaysia and the civil and Islamic legal systems that as profession. The discussion and deliberations, undertake by a scholar had great mind and repute, are succint and illustrative and at a times intellectually provocative and challenging.